Prediction of The Global Recession's Effects on Indonesia's Economy in 2023 - Vella Anggresta; Heru Subiyantoro; Pudji Astuty (Future Science / FSH-PH Publications, 2023)
The global economy in recent years has shown a downward trend and is predicted by the World Bank to become a recession in 2023. As a global economic phenomenon, this condition will affect every country, including Indonesia’s. This study analyzed the ability of Indonesia's economic fundamentals in a qualitative descriptive and literature study based on five indicators of the economic crisis, namely: economic growth, the exchange rate of the rupiah against the US dollar; inflation; economic growth; and total foreign debt, by comparing conditions during the economic crisis in 1998 and 2008, with Indonesia's current economic situation (in 2022). The results of this study indicated that Indonesia's economic condition is considered quite ready and stable to face the threat of a global economic crisis in 2023. However, as a country that depends on global economic relations, Indonesia will indirectly or directly impact the economic fluctuations and inflation that occur in many countries during the crisis because the economic crisis will have social and political impacts. This research suggests that Indonesia should focus on maintaining economic continuity in the real sector, maintaining the supply of basic needs at the community level, building economic independence by encouraging more production, and supporting political and security stability.